Próba podejścia transdyscyplinarnego do żałoby zwierząt. Rozważania o zwierzęcej śmierci – między naukowością a osobistym doświadczeniem - Lange, Łucja (Zoophilologica. Polish Journal of Animal Studies, 2019)
The aim of the article is to present the dilemmas that researchers may face, combining more than one research perspective. We are starting from sociological or ethnological research that focus on the stories of animals’ caregivers after the animal experiencing death of a companion. They are anthropomorphic and close to the urban legends. Although correct from the point of view of social research, they do not take into account the biological and psychological context. Examining the experience of mourning animals other than human requires giving a voice to those who will not answer researchers’ questions. However, having a wider perspective and trying to do transdisciplinary science, it becomes a duty to take into account even such knowledge, which will be inconsistent with the current research results. Another problem arises when trying to combine these points of view in such a way as not to alienate the respondents or researchers and at the same time get the most probable version of reality.